The change imperative : creating the next generation NGO - Ronalds, Paul, 1971- (Kumarian Press, 2010)
Whether they like it or not, relief and development NGOs are in the midst of a revolution. Faced with the challenge of managing their growing influence in international politics, these Organizations are making operational decisions that will determine their survival. Those that find themselves hampered by the increased politicization of aid and demands on their accountability; those that struggle to define their work in a world that has only recently begun to recognize their authority, will fail to meet their goals. Those that are committed to flexibility, learning new technologies and rethinking their strategies and structure will see their organizations succeed. Author Paul Ronalds brings his experience as Deputy CEO of World Vision Australia to other NGO managers in The Change Imperative, guiding them through the challenges they must overcome to maintain effectiveness in the 21st century. He covers the practical issues leaders are facing in areas such as advocary, fundraising. technology, financing and human resources, but also the more ambiguous issues: legitimacy, state sovereignty and political analysis. Ronalds' book is a must-have for both students and managers pursuing influential careers in charitable, development and aid organizations. -- Back cover.